Strategies of the Bimbo family economic group - Pérez-Sánchez, Beatriz (2021)
In the Mexican food industry, the presence of large companies or family economic groups in various branches is identified. In this research, the development of the Bimbo Family Group is particularized, which, parallel to its growth in the national market, began its internationalization process in 1984, prior to the establishment of the trade liberalization policy. Objective: to analyze the corporate structure and competitive strategies used by Grupo Bimbo to organize itself as a successful economic group and consolidate itself in the national and international market. Methods: historical-analytical and descriptive methods were used; secondary sources: literature review, company website, Annual Reports and Reports of Grupo Bimbo sent to the Mexican Stock Exchange. Results: in Bimbo's growth, its strategies stand out: financing, acquisitions, alliances, divestments and geographic coverage that have allowed it to diversify and expand its product portfolio with new brands and consolidate itself in the Mexican market, as well as its income and participation in new international markets. Conclusions: By consolidating its presence in the market, Grupo Bimbo has concentrated and centralized its capital in the food sector, and constitutes a successful economic group with a greater global presence.